2017
DOI: 10.2472/jsms.66.906
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Magnesium AZ31 by Using Scanning Cyclic Press and the Improvement Effect on Fatigue Properties

Abstract: A new surface modification technique, scanning cyclic press (SCP), was developed. SCP scans a metal surface with a vibrating indenter under precise loading control based on servo fatigue testing machine and can apply a variable cyclically compressive load. This study applied SCP to magnesium alloy AZ31 to investigate the effect on fatigue properties. After applying SCP, the surfaces of specimens were observed by using a laser scanning microscope and uniaxial push-pull fatigue tests were conducted. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This indicated that the fatigue strength of the surface fracture of machine-finished AZ31 was around this stress level. In mirror-polished specimens, the fracture origin located at the surface except the specimen unbroken at 80 MPa (Fujimura et al, 2017). It showed that the fatigue strength of the surface fracture of the machine-finished specimen was higher than that of the mirror-polished specimen.…”
Section: Fatigue Test Results and Fracture Surface Observationsmentioning
confidence: 94%
See 4 more Smart Citations
“…This indicated that the fatigue strength of the surface fracture of machine-finished AZ31 was around this stress level. In mirror-polished specimens, the fracture origin located at the surface except the specimen unbroken at 80 MPa (Fujimura et al, 2017). It showed that the fatigue strength of the surface fracture of the machine-finished specimen was higher than that of the mirror-polished specimen.…”
Section: Fatigue Test Results and Fracture Surface Observationsmentioning
confidence: 94%
“…This improvement effect is the result of SCP modifying the surface layer of the machined specimen. In our previous study, we applied SCP to the surface of a mirror-polished specimen (Fujimura et al, 2017). The microstructure observation at the cross-section of the SCP-treated specimen showed that the mesh-patterned region, which was finer than the matrix (grain size: 45 µm) as shown in Fig.…”
Section: Fatigue Test Results and Fracture Surface Observationsmentioning
confidence: 97%
See 3 more Smart Citations